Integration of Islamic Education Curriculum Management with Local Content to Strengthen the Moral Character Religio-Cultural Adaptivity of Elementary School Students - Diah Widiawati; Kartimi Kartimi; Iman Subasman; Abdul Karim; Rahmatullah Rahmatullah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2026)
Islamic education in elementary schools plays a vital role not only in building students’ cognitive religious knowledge but also in shaping their moral character deeply rooted in local culture and values. This study explores how the Islamic education curriculum is managed and integrated with local content at SDIT Kasih Ibu, East Karawang District, and examines its effectiveness in strengthening students’ moral development. Employing a qualitative case study approach grounded in curriculum integration theory (Beane, 1997) and local wisdom-based character education (Suyanto, 2018), data were gathered through in-depth interviews with principals, Islamic education teachers, and parents, participant observation of daily learning activities and school routines, and analysis of curriculum documents, lesson plans, and moral development records. Data were analyzed using Miles and Huberman’s interactive model strengthened by the constant comparative technique. The findings reveal three interconnected strategies: curriculum mapping that synergizes Islamic values such as akhlaq karimah and tauhid with local Karawang elements including gotong royong, silih asih, and traditional arts into thematic learning; positioning teachers as moral exemplars through consistent uswah hasanah practices and reflective mentoring; and the development of a habituative school culture via extracurricular activities, daily routines, and hidden curriculum such as subuh pengajian, environmental care, and peer mediation. These holistic and contextual approaches demonstrate that moral strengthening extends far beyond classroom instruction, permeating the entire school environment. Ultimately, this study concludes that integrative curriculum management aligned with local wisdom effectively nurtures students who are religiously grounded, culturally rooted, and socially adaptive, offering valuable insights for sustainable character education in Indonesia.